Comparison of Cardiac MRI Tissue Tracking and Myocardial Tagging for Assessment of Regional Ventricular Strain - Harrild, David M. (Int J Cardiovasc Imaging, 2012)
This study sought to compare regional measures of ventricular strain by tissue tracking (TT) to those derived from myocardial tagging (MT) within cardiac MR (CMR), in normal subjects and patients with hypertrophic cardiomyopathy. CMR images from 13 normal subjects and 11 subjects with hypertrophic cardiomyopathy were retrospectively analyzed. For each subject, equivalent mid-papillary level short-axis cine steady-state free precession and MT slices from the same examination were evaluated. The time to peak circumferential strain and magnitude of the peak strain were calculated for 6 matched left ventricular segments. Data from 24 slices (n=144 segments) were compared. The mean difference between techniques in magnitude of peak strain and time to peak strain was 1±9% and 1±58 ms, respectively. The mean difference in the standard deviation of time to peak strain within a slice was 0±19 ms (mean cardiac cycle duration 1013±204 ms). Bland-Altman analysis showed closer agreement in time to peak strain than peak strain magnitude. Measurements of segmental time to peak strain by TT and MT were in close agreement; agreement for the magnitude of peak segmental strain was more modest. The TT approach does not add to CMR examination time and may be a useful tool for the assessment of ventricular synchrony.